Inhibition of ZIP4 reverses epithelial-to-mesenchymal transition and enhances the radiosensitivity in human nasopharyngeal carcinoma cells - Zeng, Qi; Liu, Yi-min; Liu, Jun; Han, Jian; Guo, Jian-xin; Lu, Shun; Huang, Xue-mei; Yi, Ping; Lang, Jin-yi; Zhang, Peng; Wang, Chun-ting (Cell death & disease, 2019)
ZIP4 is a zinc transporter involved in epithelial cell morphology and migration in various cancers. In the epithelial-to-mesenchymal transition (EMT), epithelial cells transition into mesenchymal cells. The EMT plays a crucial role in invasiveness and metastasis during tumorigenesis. The aim of this study was to investigate the role of ZIP4 in the invasiveness and radiosensitivity of human nasopharyngeal carcinoma (NPC). In this study, results from 99 human patients with NPC showed that ZIP4 expression levels significantly correlated with a higher TN (tumor, lymph node) classification, as well as shorter overall survival (OS), recurrence-free survival (RFS), and distant metastasis-free survival (DMFS). Forced overexpression of ZIP4 promoted the migration and invasion of C666-1 cells through regulation of the EMT process. In contrast, ZIP4 silencing by lentivirus-mediated shRNA inhibited the EMT and metastasis of C666-1 cells in vitro and in vivo. Importantly, protein microarray analyses showed that downregulation of ZIP4 in C666-1 cells resulted in the decreased abundance of phosphoinositide 3-kinase (PI3K) p85 (Tyr607), phosphorylated (p)-Akt (Ser473), phosphorylated (p)-Akt (Thr308), and phosphorylated glycogen synthase kinase 3β (pGSK3β; Ser9). These data suggest that ZIP4 induces the EMT and promotes migration and invasion via the PI3K/Akt signaling pathway in NPC. Moreover, ZIP4 silencing significantly enhanced radiation-induced apoptosis and growth inhibition of human C666-1 cells in vitro and enhanced the antitumor activity of ionizing radiation (IR), leading to tumor growth inhibition in vivo. These results demonstrate that ZIP4 is a novel prognostic factor for malignant NPC progression. More importantly, targeting ZIP4, along with radiotherapy, may be an effective new treatment for NPC.